Within‐species phenotypic diversity enhances resistance to stress ‐ A case study using the polymorphic species Bosmina longirostris. Issue 5 (20th August 2019) - Adamczuk, Małgorzata; Mieczan, Tomasz
Abstract: Bosmina longirostris is a polymorphic cladoceran, widely distributed throughout the world in temperate and tropical climates, where it colonises all kinds of freshwater bodies regardless of their trophy, acidification, or salinity. In this paper, we test the hypothesis that the ability of B. longirostris to colonise new freshwater bodies results from their maintenance of morphotypes with different life histories. To test the above hypothesis, the life histories of four morphotypes of B. longirostris were analysed through daily observations of individuals cultured separately under uniform optimal conditions. We demonstrated that these morphotypes differed in somatic growth, reproductive effort, lifespan, and fitness, and differences in life histories among morphotypes resulted from the trade‐offs between these parameters. Next, we examined the role of distinct morphotypes (each with specific life‐history) in populations subjected to stress: we maintained two populations of B. longirostris under biotic stress (the presence of invertebrate predators) or abiotic stress (elevated salinity). At the end of the experiment these populations differed from one another in the relative density of morphotypes in comparison with the population cultured in the optimal environment. In populations that suffered from predatory pressure we found an increase in the relative density of morphotypes that grew considerably quicker, had a shorter lifespan, reproduced infrequently but delivered many offspring at each reproductive event. In populations that suffered from elevated salinity, we observed an increase in morphotypes that exhibited low reproductive effort but had the highest survival. Simultaneously, with phenotypic regrouping of populations, morphotypes adapted to novel conditions by altering the expression of life‐history traits. The observed switches in the phenotypic structure of B. longirostris suggest that the persistence of morphotypes with different life histories is beneficial to populations colonising varying environments and their relative abundances in a population are conditioned by the diverseness of local stressors.